2016
DOI: 10.1016/j.cpr.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the psychological correlates of adjustment outcomes in adults with inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a chronic long term condition which poses significant psychosocial adjustment challenges. The purpose of this review was to systematically identify psychological factors related to adjustment in adults with IBD with the aim of suggesting evidence based targets that may be modifiable though psychological intervention. Twenty five studies met inclusion criteria and were included in the systematic review and a narrative synthesis was conducted. A wide range of psychological var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…Alexithymia has been associated with an expanding range of somatic pathologies such as inflammatory bowel disease, myocardial infarction, chronic respiratory diseases, dermatologic conditions, chronic pain, neuromuscular disorders, diabetes and food allergy (). It has been found to increase unhealthy behaviours and susceptibility to organic diseases notably immune‐mediated disorders via physiological, behavioural, cognitive or social pathways from childhood leading to adverse outcomes in adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexithymia has been associated with an expanding range of somatic pathologies such as inflammatory bowel disease, myocardial infarction, chronic respiratory diseases, dermatologic conditions, chronic pain, neuromuscular disorders, diabetes and food allergy (). It has been found to increase unhealthy behaviours and susceptibility to organic diseases notably immune‐mediated disorders via physiological, behavioural, cognitive or social pathways from childhood leading to adverse outcomes in adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on different chronic diseases highlighted the need to develop and test alexithymia interventions and examine their effects on important disease‐related variables (e.g. HRQL, symptoms) . A controlled study found a significant decrease in TAS scores among cardiac patients in psychological treatment but not in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with medically complex and chronic diseases often have comorbid mental health conditions and psychosocial challenges that, if adequately addressed, are associated with improved health outcomes. [5][6][7][8][9][10] Integrating psychosocial care into IBD practices represents an important step toward "whole-person" care. 11 For the purposes of this review, "psychosocial" is defined as psychological symptoms, illness perception, coping, health behaviors, environmental stress, and social/racial/ethnic factors that can impact disease.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…This reciprocal interaction is likely to be mediated by cognitive, behavioural, and emotional responses. Our findings suggest that by identifying and addressing unhelpful responses with cognitive behaviour therapy, both mood and reports of disease activity may improve (Jordan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%